Review with quality synthesis about the experiences of boys and girls who are bullies at school (Research, Society and Development, 2022)
This study focused on the issue of the practice of school bullying and the differences between boys and girls. We aim to synthesize and interpret qualitative primary studies on the practice of school bullying. Methodologically, we consulted the PsycINFO, SCOPUS, Web of Science, SciELO databases and the periodic International Journal of Bullying Prevention. The guiding question are: what is the qualitative scientific evidence on the experiences of boys and girls who practice bullying at school? Six articles were included in the review. It was found that boy’s practice more physical type bullying and girls use indirect techniques to attack colleagues. Aggressors, in general, have the following characteristics: high sense of superiority; desire for control; seeking power and status; obtaining pleasure; aggressiveness as a constituent of its image; awareness of the practice of bullying. In a further synthesis a reflective critique of the reviewed findings was presented. Although the number of references included in the review is limited, this meta-synthesis is relevant as it sheds light on the experiences of girls and girls who practice bullying, and this evidence may guide antibullying intervention actions.